(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2016)
Adolescent pregnancy, which is detrimental to the health of mother and child, is a common public health problem worldwide. It is one of the key issues concerning reproductive health of women not only in developing countries but also in developed countries. There is growing awareness that early child bearing has multiple consequences in terms of maternal health, child health and over all well-being of the society. The purpose of the article is to review current trends and issues on adolescent pregnancy to update the practitioners. The readers are provided with more recent data on adolescent sexuality, child bearing as well as suggestions for addressing the challenges of teenage pregnancy. Chatt Shi Hosp Med Coll J; Vol.15 (1); Jan 2016; Page 53-56